Pelatihan Pembuatan Eco-Enzyme Aromatik Sebagai Solusi Permasalahan Limbah Kopi di Gustaf Coffee Jember - Alwi, Annisa Lutfi; Asmono, Sepdian Luri; Wardana , Rudi; Setyoko, Ujang; Kusumaningtyas, Rizky Nirmala (Agrimas : Jurnal Pengabdian Masyarakat Bidang Pertanian, 2025)
Waste from coffee husks has risen alongside increased coffee production. Gustaf Coffee, a new startup, produces an average of 3 tons of green beans each year using both wet and natural processing methods. Post-harvest processing of coffee generates solid waste in the form of coffee husks, making up about 40% of the weight of coffee cherries. Their high water content of 75-80% encourages microbial growth, which may contribute to environmental pollution. Currently, Gustaf Coffee is accumulating coffee husk waste and allowing it to decompose naturally into compost. To optimize the utilization of this waste, the proposed initiative involves providing training for the conversion of coffee fruit skin waste into eco-enzymes. Eco-enzymes are organic solutions produced through the fermentation of vegetable and fruit skins, combined with enzymes and various minerals, with the fermentation process extending over three months. The objective of this community service activity is to educate both the community and our partners on methods to enhance the value of coffee husk waste. The planned activities will encompass coordinating preparations with partners, conducting informational sessions on organic coffee cultivation and waste processing, offering training on producing eco-enzymes, and concluding with a monitoring and evaluation phase. After receiving training on eco-enzyme processing techniques, all participants (100%) expressed interest in transforming agricultural waste into valuable products. This assertion was substantiated through the monitoring and evaluation process, which included direct inquiries and a questionnaire designed to gather quantitative data.